Increased Environment-Related Metabolism and Genetic Expression in the In Vitro Matured Mouse Oocytes by Transcriptome Analysis - Zhang, Hao-Lin; Xu, Yi; Ju, Jia-Qian; Pan, Zhen-Nan; Liu, Jing-Cai; Sun, Shao-Chen (Frontiers in Cell and Developmental Biology, 2021)
Infertility in humans at their reproductive age is a world-wide problem. Oocyte in vitro maturation (IVM) is generally used in such cases to acquire the embryo in assisted reproductive technology (ART). However, the differences between an in vivo (IVO) and IVM culture environment in the RNA expression profile in oocytes, remains unclear. In this study, we compared the global RNA transcription pattern of oocytes from in vitro and in vivo maturation. Our results showed that 1,864 genes differentially expressed between the IVO and IVM oocytes. Among these, 1,638 genes were up-regulated, and 226 genes were down-regulated, and these changes were mainly divided into environmental adaption, metabolism, and genetic expression. Our detailed analysis showed that the expression of genes that belonged to metabolism-related processes such as energy metabolism, nucleotide metabolism, and carbohydrate metabolism was changed; and these genes also belonged to organismal systems including environmental adaptation and the circulatory system; moreover, we also found that the relative gene expression of genetic expression processes, such as protein synthesis, modification, and DNA replication and repair were also altered. In conclusion, our data suggests that in vitro maturation of mouse oocyte resulted in metabolism and genetic expression changes due to environmental changes compared with in vivo matured oocytes.